Differentiated Mathematics Teaching and Learning Media: Systematic Literature Review 2015-2024 - Maullina, Eka Siti; Usodo, Budi; Fitriana, Laila; Nurhasanah, Farida (Proceeding International Conference on Mathematics and Learning Research, 2024)
Differentiated Mathematics Teaching and Learning Media Research allows students to actively participate, ask questions, express opinions, and improve their mathematics skills. Teachers can apply differentiated learning with learning media, both concrete and digital learning media. This study aims to examine differentiated mathematics teaching and learning media related to the year of publication, mathematics topics, education levels, regional distribution, and mathematics learning media so that concise literature can be obtained regarding the latest facts regarding the role of media stored in and differentiated mathematics learning over the past 10 years based on the Scopus, ERIC, and Sinta databases. This research is a Systematic Literature Review (SLR) study. The methodology used is Systematic Review and Meta-Analysis (PRISMA), given limitations in the form of inclusion and exclusion criteria. The results of the study showed that in 2015-2024 there were170 articles related to the research topic; based on the inclusion criteria and exclusion criteria, there were 11 articles that met the criteria. The most widely used topic is the topic of fractions, which is 3 articles, then statistics and geometry each as many as 2 articles; and the topics of measurement, graphs, trigonometry, arithmetic, data, transformation, integers and measurement, and scales each 1 article and the most research was conducted on improving junior high schools, with a percentage of 38%. It was found that Indonesia ranks first with the number of articles as many as 6 articles, and the media most developed or used in differentiated mathematics learning is modules.